Bioactivity of extracts from solanaceae against zabrotes subfasciatus - Gonçalves, Gabriel Luiz Padoan; de LIRA, Simone Possedente; Gissi, Danilo Soares [UNESP]; Vendramim, José Djair (Universidad Nacional de Colombia, 2021)
The botanical family Solanaceae has many species producing compounds with insecticidal properties, e.g. nicotine and capsaicin, which are used for pest management in agriculture. This fact provides perspectives to identify insecticidal compounds in Brazilian native species of Solanaceae. In this study, we performed a screening with 25 ethanolic extracts from 17 Solanaceae species in order to evaluate their bioactivity against the Mexican bean weevil, Zabrotes subfasciatus (Coleoptera: Chrysomelidae: Bruchinae). The bioactivity of Solanaceae ethanolic extracts (2,500 mg kg-1) was tested with residual contact bioassays. Adults of Z. subfasciatus were exposed to treated bean grains, and adult mortality, oviposition, F1 progeny and damages on grains were quantified. Most of the ethanolic extracts from Solanaceae reduced the number of eggs per sample, the egg-adult viability, the F1 progeny and the damages on bean grains promoted by Z. subfasciatus, but none of them interfered on its sex ratio. Ethanolic extract from leaves of Solanum lycocarpum A. St.-Hil promoted the most promissory effects on Z. subfasciatus. This ethanolic extracts can be a suitable alternative to control Z. subfasciatus in stored beans, mainly for small farmers and organic farmers.
Bioactividad de extractos de solanaceae contra zabrotes subfasciatus
Keywords: Botanical insecticides; Mexican bean weevil; Phaseolus vulgaris